Study some aspects of transportation and traffic in the city of Baghdad - Mirza, Muhammad Ali (Al-Adab Journal, 2015)
The research deals with the analyzing of some aspects of transportation and traffic in Baghdad capital city. The city faces this acute problem with other associated urban problems now. The economic – social and physical structure decayed due to these problems.The research based on objective analysis approach in analyzing formal statistical data and field observations.The content of the study involves four aspect .Spatial and population growth of the city .Characteristics of urban transportation system of the city.Analysis of some traffic and transportation problems in the city .Policies for solve the problem